Reverse list of lists using foldr Haskell - list

I'm trying to reverse list of lists in Haskell by using foldr. There is an example of what I want to do:
> reverse'' [[1,2,3],[3,4,5]]
[[5,4,3],[3,2,1]]
And my code (it is not working):
reverse'':: [[a]]->[[a]]
reverse'' x = foldr (\n acum -> acum:(foldr(\m acum1 -> acum1++[m])) [] n) [[]] x
My IDE reports me an error at the start of the second foldr.

To analyse your current solution, I've broken down your one-liner into some helper functions, with their type deduced based on their composition:
reverse'':: [[a]] -> [[a]]
reverse'' x = foldr f [[]] x
where
f :: [a] -> a -> [a]
f n acum = acum : reverse n
reverse :: [a] -> [a]
reverse n = foldr append [] n
append :: a -> [a] -> [a]
append m acum = acum ++ [m]
When I try to compile the above, ghc complains with the following error for the type signature of reverse'':
Expected type: [[a]] -> [[a]] -> [[a]]
Actual type: [[a]] -> [a] -> [[a]]
I did some digging, and in order for reverse'' to have the type [[a]] -> [[a]], the function f needs to have the type [a] -> [[a]] -> [[a]]. However the current f has type [a] -> a -> [a], or in this case [[a]] -> [a] -> [[a]].
The following has the correct type, but inserts an extra [] value into the start of the array, due to the starting value of the accumulator:
reverse'':: [[a]] -> [[a]]
reverse'' x = foldr f [[]] x
where
f :: [a] -> [[a]] -> [[a]]
f n acum = acum ++ [reverse n]
reverse :: [a] -> [a]
reverse n = foldr append [] n
append :: a -> [a] -> [a]
append m acum = acum ++ [m]
The final solution
By changing the initial accumulator value to the empty list [], as opposed to a list of an empty list [[]], we end up at a working solution:
reverse'':: [[a]] -> [[a]]
reverse'' x = foldr f [] x
where
f :: a -> [a] -> [a]
f n acum = acum ++ [reverse n]
reverse :: [a] -> [a]
reverse n = foldr append [] n
append :: a -> [a] -> [a]
append m acum = acum ++ [m]
As a single line
If you really want this as a one-liner, here it is:
reverse'' :: [[a]] -> [[a]]
reverse'' = foldr (\n acum -> acum ++ [foldr (\m acum1 -> acum1 ++ [m]) [] n]) []
With working:
append m acum = acum ++ [m]
append = \m acum1 -> acum1 ++ [m]
reverse n = foldr append [] n
reverse = \n -> foldr append [] n
reverse = foldr append []
reverse = foldr (\m acum1 -> acum1 ++ [m]) []
f n acum = acum ++ [reverse n]
f = \n acum -> acum ++ [reverse n]
f = \n acum -> acum ++ [foldr (\m acum1 -> acum1 ++ [m]) [] n]
reverse'':: [[a]] -> [[a]]
reverse'' x = foldr f [] x
reverse'' x = foldr (\n acum -> acum ++ [foldr (\m acum1 -> acum1 ++ [m]) [] n]) [] x
reverse'' = foldr (\n acum -> acum ++ [foldr (\m acum1 -> acum1 ++ [m]) [] n]) []
Appendix: An explicitly recursive solution
Here is an explicitly recursive solution (i.e. not using a fold), with definitons of map and reverse provided.
reverse :: [a] -> [a]
reverse (x:xs) = reverse xs ++ [x]
reverse [] = []
map :: (a -> b) -> [a] -> [b]
map f (x:xs) = f x : map f xs
map _ [] = []
reverse'' :: [[a]] -> [[a]]
reverse'' ls = reverse $ map reverse ls

Related

How can I only slice the list when the function is not true in haskell?

I would like to slice my list when the function is not true, but I do not have an idea what I have to give back in the otherwise case. Do you have any idea ?
Example :
sliceBy odd [1..5] == [[1],[2],[3],[4],[5]]
sliceBy odd [1,3,2,4,5,7,4,6] == [[1,3],[2,4],[5,7],[4,6]]
sliceBy even [1,3,2,4,5,7,4,6] == [[],[1,3],[2,4],[5,7],[4,6]]
sliceBy :: (a -> Bool) -> [a] -> [[a]]
sliceBy _ [] = []
sliceBy _ [x] = [[x]]
sliceBy f (x:xs)
| f x = [x] : sliceBy f xs
| otherwise = ??
You can make use of span :: (a -> Bool) -> [a] -> ([a], [a]) and break :: (a -> Bool) -> [a] -> ([a], [a]) to get the longest prefixes where the list does/does not satisfy a given predicate. You thus can use this to make two functions sliceBy and sliceByNot that call each other:
sliceBy :: (a -> Bool) -> [a] -> [[a]]
sliceBy _ [] = []
sliceBy f xs = … : …
where (xp, xnp) = span f xs
sliceByNot :: (a -> Bool) -> [a] -> [[a]]
sliceByNot _ [] = []
sliceByNot f xs = … : …
where (xnp, xp) = break f xs
Where you need to fill in the … parts. The two functions thus should call each other.

infinite type error reversing a list in Haskell

I'm trying to implement the reverse of a list:
myLast :: [a] -> a
myLast [] = error "No end for empty lists!"
myLast [x] = x
myLast (_:xs) = myLast xs
myReverse :: [a] -> [a]
myReverse (x:xs) = myLast xs + myReverse xs
but I get this error:
/workspaces/hask_exercises/exercises/src/Lib.hs:42:32: error:
* Occurs check: cannot construct the infinite type: a ~ [a]
* In the second argument of `(+)', namely `myReverse xs'
In the expression: myLast xs + myReverse xs
In an equation for `myReverse':
myReverse (x : xs) = myLast xs + myReverse xs
* Relevant bindings include
xs :: [a] (bound at src/Lib.hs:42:14)
x :: a (bound at src/Lib.hs:42:12)
myReverse :: [a] -> [a] (bound at src/Lib.hs:41:1)
|
42 | myReverse (x:xs) = myLast xs + myReverse xs
| ^^^^^^^^^^^^
What does it mean that cannot construct the infinite type: a ~ [a]? I get this error a lot and would like to understand what it means.
The (+) :: Num a => a -> a -> a function adds two numbers (of the same type) together. So for example if a ~ Int, it will add two Ints together, but not an Int and a [Int].
But even if the (+) operator for example would prepend an item to a list, it would still not reverse the list correctly: your function has no base case what to do for an empty list, and your recursive list does nothing with the first item x of the list (x:xs).
A simple way to reverse:
myReverse :: [a] -> [a]
myReverse [] = []
myReverse (x:xs) = myReverse xs ++ [x]
But that is not efficient: appending two items will take linear time in the size of the left list. You can work with an accumulator: a parameter that you each time update when you make a recursive call. This looks like:
myReverse :: [a] -> [a]
myReverse [] = go []
where go ys (x:xs) = …
where go ys [] = …
where filling in the … parts are left as an exercise.
You have
myLast :: [a] -> a
myReverse :: [a] -> [a]
myReverse (x:xs) = myLast xs + myReverse xs
\___a___/ \____[a]___/
(x:xs) :: [a]
---------------
x :: a
xs :: [a] xs :: [a]
myLast :: [a] -> a myReverse :: [a] -> [a]
------------------------- ----------------------------
myLast xs :: a myReverse xs :: [a]
myReverse (x:xs) :: [a]
but
> :t (+)
(+) :: Num a => a -> a -> a
which means that the type of the thing on the left of + and the type of the thing on the right must be the same.
But they can't be: as we just saw above, in your code the first (of myLast xs) is some type a, and the second (of myReverse xs) is [a] the list of those same as.
These two can't be the same, because it would mean
a ~ [a] OK, this is given to us, then
a ~ [a] we can use it, so that
--------------
a ~ [[a]] this must hold;
a ~ [a] we know this, then
--------------
a ~ [[[a]]] this must also hold; and
a ~ [a] ........
-------------- ........
a ~ [[[[a]]]] ........
.........................
and so on ad infinitum, thus making this a an "infinite" type. Hence the error.
You could fix it by replacing the + with
(+++) :: a -> [a] -> [a]
and implementing it to do what you need it to do.
You will also need to fix your off-by-one error whereby you completely ignore the first element in the received input, x.

own nub function - how to use foldl/foldr?

Here is my own implementation of nub (remove duplicates):
nub :: (Eq a) => [a] -> [a]
nub lista = nub_rec lista []
where
nub_rec :: (Eq a) => [a] -> [a] -> [a]
nub_rec [] acc = acc
nub_rec (x:xs) acc = nub_rec (filter (\y -> if y == x then False else True) xs) (x:acc)
I consider how to use foldr/foldl to implement nub, could you help me ? I can't see a way.
First, your implementation of nub is bit more complex than it needs to be (and it reverses the order of elements in the list). Here's a simpler one:
myNub :: Eq a => [a] -> [a]
myNub (x:xs) = x : filter (/= x) (myNub xs)
myNub [] = []
Now, if we want to use foldr to write a function that will output, not just an "aggregate" but a full list, it's useful to first have a look at the simplest foldr-based function that takes in a list and spits out a list:
myNoop :: [a] -> [a]
myNoop l = foldr (\ x xs -> x : xs) [] l
Given that, the filter must be inserted somewhere. Since I assume this is a homework, I'll leave that to the OP as an exercise :)
Solution only with filter and foldr without direct (or self) recursion:
removeDuplicates :: Eq a => [a] -> [a]
removeDuplicates = foldr (\z ys -> z : filter (/= z) ys) []

How to insert a list in a list in all possible ways?

I am trying to enumerate all the possible merges of two lists.
In example inserting "bb" into "aaa" would look like
["bbaaa", "babaa", "baaba", "baaab", "abbaa", "ababa", "abaab", "aabba", "aabab", "aaabb"]
What I currently did is this
import Data.List
insert'' :: Char -> String -> [(String, String)] -> String
insert'' _ _ ([]) = []
insert'' h b ((x, y):xs) =
(x ++ [h] ++ (insert' (b, y))) ++ (insert'' h b xs)
insert' :: (String, String) -> String
insert' ([], ys) = ys
insert' (xs, ys) =
insert'' h b lists
where
h = head xs
b = tail xs
lists = zip (tails ys) (inits ys)
This returns for ("aaa", "bb")
"bbaaababaaabaababbaababaababbabababb"
a concatenated string, I tried making it a list of strings, but I just cannot wrap my head around this function. I always seems to get infinite type construction.
How could I rewrite the function, so it would return a list of strings?
An other implementation idea as in Daniel Wagners first post is to choose in each step a element from one of the lists and prepending it to the results generated by the function called with only the remaining parts of the list:
interleave :: [a] -> [a] -> [[a]]
interleave xs [] = [xs]
interleave [] ys = [ys]
interleave xs#(x : xs') ys#(y : ys') =
map (x :) (interleave xs' ys) ++ map (y :) (interleave xs ys')
For your intial example this produces:
ghci> interleave "bb" "aaa"
["bbaaa","babaa","baaba","baaab","abbaa","ababa","abaab","aabba","aabab","aaabb"]
Here is one implementation idea: for each element in the first list, we will choose (nondeterministically) a position in the second list to insert it, then recurse. For this to work, we first need a way to nondeterministically choose a position; thus:
choose :: [a] -> [([a], [a])]
choose = go [] where
go before xs = (before, xs) : case xs of
[] -> []
x:xs -> go (x:before) xs
For example:
> choose "abcd"
[("","abcd"),("a","bcd"),("ba","cd"),("cba","d"),("dcba","")]
Now we can use this tool to do the insertion:
insert :: [a] -> [a] -> [[a]]
insert [] ys = [ys]
insert (x:xs) ys = do
(before, after) <- choose ys
rest <- insert xs (reverse after)
return (before ++ [x] ++ rest)
In ghci:
> insert "ab" "cde"
["abcde","aebcd","adebc","acdeb","cabde","caebd","cadeb","dcabe","dcaeb","edcab"]
In this answer, I will give the minimal change needed to fix the code you already have (without completely rewriting your code). The first change needed is to update your type signatures to return lists of strings:
insert'' :: Char -> String -> [(String, String)] -> [String]
insert' :: (String, String) -> [String]
Now your compiler will complain that the first clause of insert' is returning a String instead of a [String], which is easily fixed:
insert' ([], ys) = [ys]
...and that the second clause of insert'' is trying to append a String to a [String] when running [h] ++ insert' (b, y). This one takes some thinking to figure out what you really meant; but my conclusion is that instead of x ++ [h] ++ insert' (b, y), you really want to run \t -> x ++ [h] ++ t for each element in insert' (b, y). Thus:
insert'' h b ((x, y):xs) =
(map (\t -> x ++ [h] ++ t) (insert' (b, y))) ++ (insert'' h b xs)
The complete final code is:
import Data.List
insert'' :: Char -> String -> [(String, String)] -> [String]
insert'' _ _ ([]) = []
insert'' h b ((x, y):xs) =
(map (\t -> x ++ [h] ++ t) (insert' (b, y))) ++ (insert'' h b xs)
insert' :: (String, String) -> [String]
insert' ([], ys) = [ys]
insert' (xs, ys) =
insert'' h b lists
where
h = head xs
b = tail xs
lists = zip (tails ys) (inits ys)
Now ghci will happily produce good answers:
> insert' ("aaa", "bb")
["bbaaa","babaa","baaba","baaab","abbaa","ababa","abaab","aabba","aabab","aaabb"]

Haskell: How to return a list of possible splits of a list

I'm trying to write a function named split that takes a list and returns a list of pairs of all the different possiblities to partition it, e.g.
split [4,3,6] = [([],[4,3,6]),([4],[3,6]),([4,3],[6]),([4,3,6],[])]
Now I wrote this
split :: [a] -> [([a],[a])]
split [] = [([],[])]
split (x:xs) = ([],(x:xs)):(zip (map (x:) (map fst split(xs))) (map snd split(xs)))
piece of code and Hugs and the interpreter of my choice gets me this
ERROR file:.\split.hs:3 - Type error in application
*** Expression : map snd split xs
*** Term : map
*** Type : (e -> f) -> [e] -> [f]
*** Does not match : a -> b -> c -> d
error message. What the heck am I doing wrong? Why would (map snd split xs) be of type
(a-> b -> c -> d)?
You've misplaced your parens. Try
split (x:xs) = ([],(x:xs)):(zip (map (x:) (map fst (split xs))) (map snd (split xs)))
Haskell doesn't use parenthesis for function calls in the same way as something like C and Java. When you write map fst split(xs) this is the same as map fst split xs, i.e. the compiler thinks that you are trying to call map with three parameters. Therefore you need to parenthise the call to split like this: map fst (split xs).
What you are effectively trying to write is a simple zipper for a list. The easiest way to implement it is
import Data.List (inits, tails)
split xs = zip (inits xs) (tails xs)
Here's an alternative definition:
splits :: [a] -> [(a, a)]
splits xs = map (flip splitAt xs) [0 .. length xs]
Admittedly, it's not very efficient, but at least it's concise :-)
Another version that's even shorter, and probably more efficient, using inits and tails from Data.List:
splits :: [a] -> [(a, a)]
splits xs = zip (inits xs) (tails xs)
Now let's have a little fun. We can write inits and tails as foldrs, where we use initsA and tailsA to represent what are known as the algebras of the folds:
inits :: [a] -> [[a]]
inits = foldr initsA [[]]
initsA :: a -> [[a]] -> [[a]]
initsA x xss = [] : map (x:) xss
tails :: [a] -> [[a]]
tails = foldr tailsA [[]]
tailsA :: a -> [[a]] -> [[a]]
tailsA x xss = (x : head xss) : xss
Using these algebras, we can further combine them:
splits :: [a] -> [([a], [a])]
splits = foldr splitsA [([], [])]
splitsA :: a -> [([a], [a])] -> [([a], [a])]
splitsA xy xyss = zip (initsA xy xss) (tailsA xy yss)
where (xss, yss) = unzip xyss
So now we have splits defined as a single foldr!